If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -4 = 2y + 20 Reorder the terms: -4 + 5y = 2y + 20 Reorder the terms: -4 + 5y = 20 + 2y Solving -4 + 5y = 20 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. -4 + 5y + -2y = 20 + 2y + -2y Combine like terms: 5y + -2y = 3y -4 + 3y = 20 + 2y + -2y Combine like terms: 2y + -2y = 0 -4 + 3y = 20 + 0 -4 + 3y = 20 Add '4' to each side of the equation. -4 + 4 + 3y = 20 + 4 Combine like terms: -4 + 4 = 0 0 + 3y = 20 + 4 3y = 20 + 4 Combine like terms: 20 + 4 = 24 3y = 24 Divide each side by '3'. y = 8 Simplifying y = 8
| 2z+4=5z | | 2+5(2+5)= | | 5x=12-32+x | | 4+9lnx=7 | | 7n-4=n+1 | | 3s+5(s+7)=99 | | x^2+8x+16=99 | | 114-d=83 | | 2*16= | | -4.6b=28.106 | | x-2x+20=12 | | -3=-6t-3 | | Y=20-6x | | -12.5+0.5p=0.9p+5.3 | | Y=x^2-17x+50 | | 139=3d+2(4d+9) | | 3r=-21 | | 32-2x=20 | | 0=-16t^2+38.8t+3 | | 8x^2-370=0 | | -10=10w-20 | | 8(x+3)=5(k-3) | | 42=6-9h | | 6x^2+2x-9=0 | | 8n-6=9n | | 0.2-0.01(x+2)=-0.03(2-x) | | 2(x-5)=4x-2(x-5) | | -7x+8=-20 | | 4(x-2)+6=6x-2(2+x) | | -1.66x+.66=-11 | | 18m+30=66 | | 2(2+4)= |